Empowering Reading Comprehension in EFL Vocational School Students through Folktale - Enni Enni; Nurul Hasanah; Syahban Mada Ali (JELITA, 2024)
Recognizing the imperative of enhancing students' comprehension in reading, especially within the context of vocational schools, the need for innovative learning approaches becomes crucial. This research aimed to assess the effectiveness of employing folktales to enhance the reading abilities of eleventh-grade students at SMK Tiwikrama Mamuju. Conducted through a pre-experimental design, the study incorporated both pretest and posttest assessments with an intervention in between. The research was conducted during the academic year 2022/2023, involving three classes comprising a total of 105 students. Utilizing purposive sampling, a sample size of 23 students was selected for the study, with the reading test serving as the primary research instrument. The data analysis unveiled a noteworthy improvement in students' mean scores, escalating from a pre-test score of 48 (categorized as very poor) to a post-test score of 75 (categorized as good). The calculated t-test value of 21.09 exceeded the critical t-table value of 2.074 at a significance level of α=0.05. This higher t-test value led to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. Consequently, the utilization of folktales demonstrated a significant enhancement in the reading abilities of eleventh-grade students at SMK Tiwikrama Mamuju.